Marine Plio/Pleistozän-Ostracoden von SE-Lakonien (Peloponnes, Griechenland) - Malz, H; Jellinek, T (Senckenbergiana Biologica, 1984)
Field work in the SE. part of Laconia, Peloponnisos Peninsula, Greece, included study of a coastal section 2 multiplied by 5 km W. of Megali Spilia where Pleistocene deposits overlie Pliocene sediments in a continuous sedimentary sequence. Two further sections inland to the E. were sampled in order to obtain more distributional data. The samples from all three sections yielded extremely rich microfaunas which mainly contain benthic Foraminifera and Ostracoda. Calcareous nannoplankton and planktonic Foraminifera occur in relatively small numbers, pointing to a palaeogeographical situations in which in the Plio-/Pleistocene Bay of Neapolis open sea conditions were limited to the S. Yet, all samples prove pure marine macro- and microfaunas, without any traces of brackish to freshwater indicators